Analisis Faktor Penentu Harga Lahan di Kota Makassar - Muhammad Faathir Nugraditama; Arifuddin Akil; Ihsan Ihsan (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2020)
Population density in urban areas results in a greater need for housing so that land availability decreases and can affect land prices. The price of land determined by the Tax Object Selling Value (NJOP) is sometimes not in accordance with what is in the field. The aim of this research is to compare the actual land value with the value determined by NJOP, to know the magnitude of the factors that affect the selling value of the land, and to map the land sale value based on the calculation of the factors that affect the land value. This research was conducted from December 2019 to March 2020 (3 months). The research location is in Makassar, Panakkukang, and Manggala Districts, Makassar City. The data used are primary data which is carried out by means of observation and interviews and secondary data which is carried out by means of agency surveys and literature studies. The analysis method used is descriptive qualitative analysis, quantitative correlation analysis, and grid-based spatial analysis. The result of the research is that there is a difference between the actual land price and the NJOP, the price difference is 40% to 60%. There are 4 variables that affect land prices, namely road classification, distance to commercial areas, number of nodes, and distance to city center. The values ​​of these variables form a map of the classification of areas that have the potential to have the highest land prices in Makassar City, such as on Urip Sumohardjo Street, Panakkukang Business District, and some areas around Veteran Street.